2015
DOI: 10.1016/j.jmbbm.2014.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Development of novel synthetic muscle tissues for sports impact surrogates

Abstract: Impact injuries are commonplace in sport and often lead to performance detriment and debilitation. Personal Protective Equipment (PPE) is prescribed as a mandatory requirement in most sports where these impacts are likely to occur, though the methods of governance and evaluation criteria often do not accurately represent sports specific injury scenarios. One of the key shortcomings of such safety test standards is the human surrogate to which the PPE is affixed; this typically embodies unrepresentative geometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Testing of auxetic foam should also extend to include tissues surrogates [e.g. 31] to provide impact scenarios which are more representative of those experienced by the human body. Finite element analysis has been applied to protective sports equipment [2][3].…”
Section: Methodsmentioning
confidence: 99%
“…Testing of auxetic foam should also extend to include tissues surrogates [e.g. 31] to provide impact scenarios which are more representative of those experienced by the human body. Finite element analysis has been applied to protective sports equipment [2][3].…”
Section: Methodsmentioning
confidence: 99%
“…5,13 This approach overlooks many important human response phenomena such as variable tissue stiffness, relative movement between structures, pressure distribution and deformation of tissues distant from the impact site. Recent research 11,12 has indicated that a structured multi-material surrogate can provide a more 'biofidelic' representation of human impact response than single-material constructions.…”
Section: Surrogate Component Selection and Definitionmentioning
confidence: 99%
“…In this research, bespoke two-part additive cure polydimethysiloxane (PDMS) silicones were developed to match the specific mechanical properties of each of skin, adipose and muscle tissues. The formulations, fabrication procedures and mechanical testing methods used for each identified simulant are detailed in Payne et al 11,12 The surrogate has been designed with the capability to incorporate either relaxed or contracted muscle tissue using the alternative formulations established in Payne et al 11 However, in the first instance, relaxed muscle tissue properties were selected for the initial surrogate as a priority since impact injuries are believed to be both more prevalent and serious when the participant is not anticipating the impact. 31 Muggenthaler et al 32 also suggested that the human monosynaptic stretch reflexes occur between 30 and 60 ms such that, in the majority of sports impacts, the most severe compressive stage is likely to have occurred before the body actively responds.…”
Section: Surrogate Component Selection and Definitionmentioning
confidence: 99%
“…Whilst computational models are valuable; physical models are also needed to facilitate the performance testing of impact protection and support the validation of computational models. Payne et al (2015a) argue that relying on computational analysis alone is unethical as it is necessary to test the physical product rather than relying on what was intended or predicted.…”
Section: Physical Modelsmentioning
confidence: 99%